Unimanual and bimanual motor performance in children with developmental coordination disorder (DCD) provide evidence for underlying motor control deficits - Grohs, Melody N. (Sci Rep, 2021)
Much of our understanding of motor control deficits in children with developmental coordination disorder (DCD) comes from upper limb assessments focusing on the dominant limb. Here, using two robotic behavioural tasks, we investigated motor control in both the dominant and non-dominant limbs of children with DCD. Twenty-six children with diagnosed DCD (20 males; mean age 10.6 years ± 1.3 years) and 155 controls were included in this cross-sectional study. Participants completed a visually guided reaching task with their dominant and non-dominant limbs and a bimanual object hitting task. Motor performance was quantified across nine parameters. We determined the number of children with DCD who fell outside of the typical performance range of the controls on these parameters and compared the DCD and control groups using ANCOVAs, accounting for age. Children with DCD demonstrated impairments in six out of nine parameters; deficits were more commonly noted in the non-dominant limb. Interestingly, when looking at individual performance, several children with DCD performed in the range of controls. These findings indicate that children with DCD display deficits in motor control in both the dominant and non-dominant limb and highlight the importance of including detailed assessments of both limbs when investigating children with DCD. They also demonstrate the variability in motor control performance evidenced by children with DCD.